From Spirits to God: Stories of the Kalash Converts from Before and After their Conversion - Kazmi, Syed Kazim Ali (Narrative Works, 2016)
Conversion to Islam is an ongoing phenomenon in the minority Kalash community in Pakistan. This article covers conversion incidents and their narration. The introduction of Islam alters the lives of the “kafir” [i.e., unbelievers in Islam] Kalash. The researcher’s intention was to discover the motivational factors behind the decision to convert as depicted through conversion narratives. Are converts under pressure from the social sphere to change religion, or it is an independent decision? How does the Islamic faith reach them? What differences do they find in their new faith as compared to the old one? Moreover, how do they adjust in the community? The data was collected from randomly selected converts whose personal narratives were recorded and transcribed. Later, the researcher analyzed the data. In this study, narrative is presented as a framework for understanding the individual converts. In the analysis, the commonalities and differences in converts’ perceptions of their new religion are discussed, as well as the trajectory of their faith alteration, their efforts of adjustment, and socio-economic development around the Kalash and its impact on the conversions.